Experimental and theoretical study on the dissociative photoionization of methyl methacrylate. (8th November 2017) - Sun, Ruirui; Meng, Qinghui; Wang, Ming; Fei, Weifei; Zhang, Yanmei; Chen, Jun; Fang, Wenzheng; Shan, Xiaobin; Liu, Fuyi; Sheng, Liusi
Abstract: The photoionization of methyl methacrylate and dissociation of its cation have been investigated by tunable vacuum ultraviolet synchrotron radiation coupled with time-of-flight mass spectrometer in the photon energy region of 9.0–15.5 eV. The ionization energy of methyl methacrylate and the appearance energies (AEs) for major fragments, C 5 H 7 O 2 +, C5 H6 O +, C 4 H 5 O 2 +, C4 H5 O +, C3 H4 O +, C3 H3 O + ( C 4 H 7 + ), C 3 H 5 +, C 3 H 4 +, C 2 H 3 O 2 +, and CH 3 + are determined to be 9.76, 10.30, 10.66, 10.51, 11.17, 10.51, 10.74, 12.88, 12.73, 12.52, and 12.82 eV, respectively, by measurement of the photoionization efficiency curves. Possible formation pathways of the major fragments are proposed based on comparison of experimental AEs and energies predicted by ab initio G3B3 calculations. Transition states and intermediates involved in the dissociation channels are also located. The majority of the proposed channels occur through isomerization prior to dissociation. Hydrogen shift and ring closing/opening are found to be the dominant processes during photofragmentaion of methyl methacrylate.